2018
DOI: 10.18203/2394-6040.ijcmph20181493
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic factors associated with low birth weight in a tertiary care hospital of Odisha

Abstract: Background: World Health Organization has defined low birth weight (LBW) as birth weight less than 2,500 grams. Giving birth to a LBW infant is influenced by several factors. Objective of the study was to measure the proportion of low birth weight babies delivered in V.S.S medical college and hospital, Burla and its association with socio-demographic factors.Methods: Hospital based cross -sectional study comprising of 1030 postnatal women who delivered single live baby in V.S.S Medical College and Hospital, Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…[ 17 ] Newborn’s sex distribution in a Bhue PK et al . [ 18 ] study (male child – 57.38%, female child – 42.62%) was similar to our study while in a study by Manna N et al . [ 19 ] male babies were 47.2%, while 52.8% were female.…”
Section: Discussionsupporting
confidence: 93%
“…[ 17 ] Newborn’s sex distribution in a Bhue PK et al . [ 18 ] study (male child – 57.38%, female child – 42.62%) was similar to our study while in a study by Manna N et al . [ 19 ] male babies were 47.2%, while 52.8% were female.…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of LBW in this study was 24%, similar to that reported in other studies with a range of 17-32% (Table 6). [31][32][33][34][35] IUGR was the predominant cause of LBW (57%) in the study as that is prevalent in South Asian Countries. 36 However, in developed countries, preterm births are the most common cause of LBW10.…”
Section: Discussionmentioning
confidence: 99%